Determinan Kunjungan Masa Nifas di Masa Pasca Pandemi di Wilayah Kerja Puskesmas Klikiran tahun 2022 - Ziyadatul Chusna Almabruroh yuni Alfi (Jurnal Ilmu Kebidanan, 2023)
Background: The postpartum period is a period of recovery for the reproductive organs after childbirth and is an important period for both mother and baby. The most common causes of maternal death in Indonesia are bleeding, hypertension in pregnancy, infections, metabolic disorders, and others. Bleeding that usually occurs during the puerperium. Through postpartum visits it is expected to be able to detect complications of the puerperium early. Purpose: to analyze the determinants of postpartum visits in the post-pandemic period in the Working Area of the Klikiran Health Center in 2022. Method: Type of correlative study with an analytic design with a cross sectional approach. Sampling technique total sampling, totaling 33 respondents. The results of the study: the results of the bivariate test showed that the variables were mother's age (p value = 0.392), education (p value = 0.266), occupation (p value = 0.052), parity (p value = 0.335), knowledge (p value = 0.015), and support (p value = 0.730) Conclusion: factors related to the completeness of postpartum visits in the Post-Pandemic Period in the Working Area of the Klikiran Health Center in 2022 are work (p value = 0.052) and knowledge (p value = 0.015). Keywords: Determinants, Visits, Postpartum Mothers